2022
DOI: 10.1055/a-1967-1350
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox Trifluoromethylation/Cyclization of N-Arylacrylamides with 4-(Difluoroamino)-1-[(trifluoromethyl)sulfonyl]pyridinium Triflate (TFSP)

Abstract: Photoredox trifluoromethylation/cyclization of N-arylacrylamides with inexpensive and stable solid trifluoromethylsulfonyl−pyridinium salt (TFSP) have been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…Over the past decade, radical fluoroalkylation/cyclization tandems have emerged as efficient approaches for constructing fluoroalkyl-containing aromatic heterocycles, contributing significantly to advancements in the field. 5 Notably, Mai et al reported a radical trifluoromethylation/cyclization tandem of N -arylcinnamamides utilizing Langlois’ reagent as the trifluoromethyl source, K 2 S 2 O 8 as the oxidant, and AgNO 3 as the catalyst, resulting in the formation of trifluoromethylated dihydroquinolinones. 5 h Recently, Zang et al developed an electrochemical trifluoromethylation/cyclization cascade employing CuOTf as the mediator, and LiClO 4 as the electrolyte to synthesize trifluoromethylated tetrahydroquinolines and dihydroquinolinones.…”
mentioning
confidence: 99%
“…Over the past decade, radical fluoroalkylation/cyclization tandems have emerged as efficient approaches for constructing fluoroalkyl-containing aromatic heterocycles, contributing significantly to advancements in the field. 5 Notably, Mai et al reported a radical trifluoromethylation/cyclization tandem of N -arylcinnamamides utilizing Langlois’ reagent as the trifluoromethyl source, K 2 S 2 O 8 as the oxidant, and AgNO 3 as the catalyst, resulting in the formation of trifluoromethylated dihydroquinolinones. 5 h Recently, Zang et al developed an electrochemical trifluoromethylation/cyclization cascade employing CuOTf as the mediator, and LiClO 4 as the electrolyte to synthesize trifluoromethylated tetrahydroquinolines and dihydroquinolinones.…”
mentioning
confidence: 99%